Reliability and validity of the ladder agility test among children - Smits-Engelsman, B.; Aertssen, W.; Bonney, E. (Pediatric Exercise Science, 2019)
Purpose: This study aimed (1) to evaluate the test-retest reliability of a new agility test among children and (2) to determine the physical performance and anthropometric variables that may influence agility performance in this population. Methods: For aim 1, participants (n=34) completed the Ladder Agility Test (LAT) twice, with a 2-week interval between the first and second test occasions. For aim 2, participants (n=125) were assessed on the LAT as well as other measures thought to be necessary for agility such as motor coordination, explosive power of the lower extremity, dynamic balance, age, and body mass index. Results: Intraclass correlation coefficient of the LAT total score was .94 (95% confidence interval, .88-.97). Cronbach alpha of .85 was found between the 4 test items. An R2 of .466 was found to represent the explained variance of the LAT total score by the predicting variables. Dynamic balance (2-legged side jumps) (P<.001), motor coordination (P<.01), and age (P<.06) were found to be the major predictors of the LAT total score. Conclusions: This study shows that the LAT is a reliable and valid field-based test that can be used to evaluate agility performance in children. Factors such as dynamic balance, motor coordination, and age may influence agility performance.